Mentoring While Black: A Testimony - Alford A. Young, Jr. (Sociologica)
After briefly exploring my experiences with being mentored, this short essay highlights how I strive to manage the politics of graduate student mentoring. Such politics involve managing the racial implications of faculty competition to attract graduate students and implementing mentoring strategies that have been uniquely informed by my own racial experiences within and outside of academia.